Calcium supplements and structure–activity relationship of peptide-calcium chelates: a review - Zhang, Minghui; Liu, Kunlun (Food science and biotechnology, 2022)
In recent years, the functional properties of peptides derived from food proteins have attracted considerable interest. Among them, bioactive peptides that can effectively bind metals have application prospects in the improvement of mineral bioavailability, and compensating for the shortcomings of the generally low bioavailability of inorganic mineral supplements. Although a reasonable understanding of structure activity relationship related to the calcium binding of peptides has been gained, physiological connections of peptides as mineral carriers to gastrointestinal uptake needs further research. Hence, this article reviews (1) the development of calcium supplements; (2) inorganic calcium sources and bone calcium; (3) source and acquisition of biologically active peptides; (4) calcium peptide chelation mechanism and structure–activity relationship; and (5) Methods for evaluating calcium bioavailability.